Experimental Development of Calcium Looping Carbon Capture Processes: An Overview of Opportunities and Challenges - Toledo, Rubens C. [UNESP]; Arce, Gretta L. A. F. [UNESP]; Carvalho, João A. [UNESP]; Ávila, Ivonete [UNESP] (MDPI, 2023)
Global warming might be mitigated if emissions were interrupted through carbon capture technologies, as there is a significant amount of comprehensive studies on them. An outline of the main gaps and trends of a technology is critical for further development. In this context, this study provides an overview of calcium looping carbon capture processes that have proven their potential and commercial viability. A bibliometric analysis is conducted on both Scopus and Web of Science database by seeking the keywords “calcium looping”, “co2 capture”, and “fluidized bed” in titles, abstracts, and keywords. Word selection was based on a list of relevant papers on the topic. These items of data have been processed and analyzed based on the number of publications and citations by emphasizing recent publication evolution, journal influence, the use of specific keywords, and co-citation. Results reveal that the European Union (EU) leads the rankings on the topic, followed by Canada. Keyword choice might have affected the number of citations. Recent studies used limestone as a sorbent and a dual fluidized bed reactor with a calciner or resistance depending on its size. Most studies are focused on technology scale-up. Although scale-up seems to be a priority, multiple studies are designed to assess the effect of steam generation and SO (Formula presented.) on the process.
Keywords: bibliometric analysis; calcium looping; carbon capture; fluidized bed; scientific gaps